The protection of monuments in the Republic of Tatarstan in modern times - Elmira Ildarovna Nazmieva, Aleksandr Alterovich Litvin, Ainaz Munirovna Mustafina, (Opción, 2019)
The article deals with the activities in the field of protection of monuments in the Republic of Tatarstan at the present stage via logical, system-structural, historical-logical, socio-cultural, comparative-legal methods. As a result, religious tourism is not associated with any particular religion, and tourists themselves pave the route depending on their interests and views. In conclusion, historical and cultural monuments are an important resource of the tourist market, therefore, with an increase in the tourist attractiveness of the object, the economic situation of the region and the country as a whole improves.